Satisfaction with therapist-delivered vs. self-administered online cognitive-behavioural treatments for depression symptoms in College Students - Richards, Derek; Timulak, Ladislav (My University, 2012)
Participants with symptoms of depression received either 8 sessions of therapist-delivered e-mail cognitive-behaviour therapy (CBT) (eCBT; n = 37), or 8 sessions of computerised CBT self-administered treatment (cCBT; n = 43). At post-treatment participants completed a questionnaire to determine what they found satisfying about their online treatment. Quantitative and qualitative analysis were employed to report outcomes. A sample of twenty-five (eCBT:10; cCBT:15) participants completed the satisfaction questionnaire. Both groups were satisfied with accessing and using an online treatment and that they had self-control over their treatment. Perceived anonymity was important for the eCBT group. For the cCBT group they found the treatment user-friendly, engaging and also a source of learning. Both groups disliked that the online treatment could at times be complicated and impersonal.
PUBLISHED
Keywords: online treatments for depression; satisfaction with treatment; qualitative analysis